Comunidades de fungos em folhedo da Mata Atlântica na região semiárida do Brasil - Costa, Loise Araujo (2014)
The Atlantic Forest has the highest biodiversity among tropical forests is one of the 34 priority areas for global conservation. Currently remains about 11% of its original area, which is composed of fragmented and geographically distant remnants. Among the microorganisms that compose forest ecosystems, fungi are important components because ensure the cycling of carbon and nutrients, however are poorly studied. The present study aimed to assess the diversity and distribution of fungi associated to leaf litter from three Atlantic Forest remnants in the semiarid region of Brazil: Brejo Paraibano-PB, Serra da Ibiapaba-CE and Serra da Jibóia-BA; and the effects of methodological aspects on mycobiota. Two expeditions were conducted in each area, during the wet season and the other in the dry season, between June/2011 and January/2013. Twenty-three samples of leaf litter, five Clusia nemorosa G. Mey and eighteen Vismia guianensis (Aubl) Choisy, were collected and submitted to the technique of particle filtration. The total volume of 9.3 mL of particle suspension was plated on two different culture media: dichloran rose bengal chloramphenicol agar (DRBC) and malt yeast extract agar (MYE). The analysis of this material yielded 6.460 colonies identified 168 taxa for which data were divided into three chapters. The first chapter evaluates the effects of time (fresh material, 07, 14, 21 and 28 d) and storage temperature (room temperature and 4°C) of the leaves of C. nemorosa plus the use of two culture media on mycobiota. Analysis of covariance indicated that the richness and the number of isolates decreased with storage, however in relation to the culture medium there was no significant difference. The storage temperature had no significant influence on the community according to the t-test. The second chapter compared the communities of fungi of C. nemorosa and V. guianensis during the wet and dry seasons. Clusia nemorosa showed higher species richness and diversity of fungi compared to V. guianensis. Similarity analysis indicated that variations in the community between plants and seasons were significant while the cluster analysis and multivariate NMDS showed seasonality factor as more decisive for the distribution of fungi. The third chapter investigated the spatial and temporal distribution of fungi associated with leaf litter community of V. guianensis present in the three remaining. Multivariate analysis NMDS revealed differences in community composition of fungi in each area and climate season and the similarity analysis indicated that the differences were statistically significant. The results of this study presented a great diversity associated with the leaf litter present in remnants of Atlantic Forest and indicate that the distribution of fungi in the environment is not random. Knowledge of the effects of biotic and abiotic factors on the distribution of saprobic fungi is fundamental to understanding the role that they play in forest ecosystems.